Genetics of type 2 diabetes. - McCarthy, M; Zeggini, E (2006)
After several years of uncertain progress, the stage is now set for a transformation in understanding the genetic landscape of type 2 diabetes. Advances in genome informatics, genotyping technology, and statistical methodology, allied to availability of large-scale clinical material, are having a salutary effect on susceptibility gene discovery. The advent of genuinely genome-wide association scans and the prospects for combining genetics with high-throughput genomics are additional sources of optimism for the future.